Cross-Cultural Communication Barriers in Organizations - Tini Mogea (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The ASEAN Economic Community (AEC) was enacted at the end of 2015, this is an opportunity for a country's skilled workforce to become professional workers in ASEAN member countries. Because the inherent nature of the enactment of the AEC is the repeal of regulations that allow the flow of goods, services, people (skilled workers), and money to be unhindered. In this condition, the role of cross-cultural communication in organizations is very strategic in creating reinforcement for the sustainability of skilled workers in pursuing their professional careers. It has become a trend that in the era of the global economy there are company activities that involve individuals/employees/managers from more than one country, both those assigned to other countries and those assigned to their own country. This condition causes cross-cultural communication to become unavoidable. In cross-cultural communication, one of the obstacles is language. Language is an extension of a culture. Differences in understanding or interpreting a word or symbol become a potential barrier to communication and this can hinder the process of business or organizational activities. For individuals who are involved in cross-cultural communication within an organization, it is recommended: 1) Increase knowledge and understanding of the culture of business partners or colleagues, 2) It is better to assume that other people who come from other cultures are different from us so as not to cause misperceptions and miscommunication with that person, 3) Apart from mastering the universal language, it is highly recommended to learn the local/regional language where we are assigned/work.